Major Aspects of the Mercury Cycle in the Negro River Basin, Amazon - da Silva, Gilmar Silverio; Bisinoti, Marcia Cristina [UNESP]; Fadini, Pedro Sergio; Magarelli, Gabriela; Jardim, Wilson F.; Fostier, Anne Helene (Soc Brasileira Quimica, 2009)
Despite the low level of industrial activity and human density, Hg concentration in the Negro River basin is relatively high. Soil enriched with naturally high Hg concentrations and atmospheric deposition are the main sources of the metal in this watershed. Differences between invasive and evasive fluxes at the water/air and soil/air interfaces indicate Hg accumulation in the basin at a rate of 39.9 t y(-1). The type of soil, which is the main source of mercury for the water bodies, the hydrological cycle with floods and dry periods, act markedly on the water redox chemistry. A complex interaction between many seasonable variables such as solar intensity, water pH, age of the naturally occurring organic matter and the hydrological cycle alter the redox characteristics of these black water bodies, thus markedly affecting the consumption of Hg-0 and the degradation of methylmercury present in the water. Although methylation is favored in black waters, photodegradation counterpoints this formation, thus regulating the methylmercury burden in the water column.
Keywords: Negro River; mercury fluxes; mercury species; black waters